2015
DOI: 10.3389/fpsyt.2015.00005
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the Commensal Microbiota: Importance in Parturition and Infant Neurodevelopment

Abstract: The body is colonized by an enormous array of microbes that are collectively called the microbiota. During quiescent periods, microbial communities within the gut are relatively resistant to change. However, several factors that disrupt homeostasis can also significantly change gut microbial community structure. One factor that has been shown to change the composition of the gut microbiota is exposure to psychological stressors. Studies demonstrate that the commensal microbiota are involved in stressor-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 69 publications
0
50
0
Order By: Relevance
“…In addition, treating animals with antibiotics to disrupt the microbiome led to changes in social behavior [49]. Stress during gestation alters the composition of the maternal microbiome and these changes are transmitted to the offspring [3,5,6]. Our study shows that offspring microbial changes persist into adulthood with males exposed to PNS demonstrating a significant difference in the gut microbiome.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, treating animals with antibiotics to disrupt the microbiome led to changes in social behavior [49]. Stress during gestation alters the composition of the maternal microbiome and these changes are transmitted to the offspring [3,5,6]. Our study shows that offspring microbial changes persist into adulthood with males exposed to PNS demonstrating a significant difference in the gut microbiome.…”
Section: Discussionmentioning
confidence: 81%
“…The mechanisms underlying this contribution include alterations in epigenetic regulation, the hypothalamic pituitary adrenal (HPA) axis, and inflammation [2]. There is increased focus on changes in the microbiome following PNS as a contributor to increased risk of neuropsychiatric disorders [3,4]. For instance, stress during gestation altered the maternal vaginal microbiome [5] and gut microbiome [6], and the composition of the gut microbiome in adult offspring [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…diet, probiotic supplementation, disease-related dysbiosis), and genomic influences that directly impact neonatal acquisition and maintenance of bacterial composition across the lifespan (Fig. 2) [59][60][61][62]. Arguably, the neonatal period represents the most developmentally-significant window for the acquisition and establishment of the GI microbiota with important immune and neurodevelopmental implications…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, in a recent study PNS was shown to affect the composition of the human infant gut microbiota over the first 110 days after birth (Zijlmans et al, 2015). Moreover, there is growing evidence that chronic stress can alter the vaginal microbial ecosystem in the mother, which in turn impairs the initial microbial colonisation of the neonatal intestine (Gur et al, 2015;JaĆĄarević et al, 2015). The maintenance of microbial diversity is important for the normal development of the CNS, as well as gastrointestinal (GI) and respiratory function (Borre et al, 2014;Collins et al, 2014;Desbonnet et al, 2015;Moreno-Indias et al, 2015).…”
Section: Introductionmentioning
confidence: 98%